THE EFFECTIVENESS OF COUNSELING WITH DEMONSTRATION METHODS ON TOOTHBRUSHING BEHAVIOR IN STUDENTS GRADE 3 SDN 2 ATU LINTANG - Itawarni, Fuja; Efendy, Ismail; Khairatunnisa, Khairatunnisa (HEARTY, 2025)
Dental and oral health is an important aspect of children's growth and development because it plays a role in supporting nutritional fulfillment. Basic Health Research data shows that dental problems in Central Aceh are still high, including in the elementary school age group. This research was conducted at SD Negeri 2 Atu Lintang which does not yet have a School Dental Health Unit (UKGS), involving all 24 3rd grade students. The results showed a significant increase in toothbrushing behavior after being given counseling using the demonstration method. Before counseling, most students were in the medium category (29.1%), while after counseling it increased to good (87.5%). The statistical test showed a value of p = 0.000 (p < 0.05), so it can be concluded that the demonstration method is effective in improving toothbrushing behavior in students. Thus, dental and oral health counseling based on the demonstration method has been proven to improve the knowledge and skills of correct brushing practices in school children. It is hoped that this activity will be carried out continuously by strengthening micro-teaching and the use of counseling media so that the effectiveness of the program is more optimal.